Comparison of the Oncological Efficacy Between Intraoperative Radiotherapy With Whole-Breast Irradiation for Early Breast Cancer: A Meta-Analysis - He, Lin; Zhou, Jiejing; Qi, Yuhong; He, Dongjie; Yuan, Canliang; Chang, Hao; Wang, Qiming; Li, Gaiyan; Shao, Qiuju (Frontiers in Oncology, 2021)
Background Intraoperative radiotherapy (IORT) and whole-breast irradiation (WBI) are both effective radiotherapeutic interventions for early breast cancer patients undergoing breast-conserving surgery; however, an issue on whether which one can entail the better prognosis is still controversial. Our study aimed to investigate the 5-year oncological efficacy of the IORT cohort and the WBI cohort, respectively, and compare the oncological efficacy between the cohorts. Materials and Methods We conducted a computerized retrieval to identify English published articles between 2000 and 2021 in the PubMed, the Web of Science, the Cochrane Library, and APA PsycInfo databases. Screening, data extraction, and quality assessment were performed in duplicate. Results A total of 38 studies were eligible, with 30,225 analyzed participants. A non-comparative binary meta-analysis was performed to calculate the weighted average 5-year local recurrence-free survival (LRFS), distant metastasis-free survival (DMFS), and overall survival (OS) in the two cohorts, respectively. The LRFS, DMFS, and OS (without restriction on the 5-year outcomes) between the two cohorts were further investigated by a comparative binary meta-analysis. The weighted average 5-year LRFS, DMFS, and OS in the IORT cohort were 96.3, 96.6, and 94.1%, respectively, and in the WBI cohort were 98.0, 94.9, and 94.9%, respectively. Our pooled results indicated that the LRFS in the IORT cohort was significantly lower than that in the WBI cohort (pooled odds ratio [OR] = 2.36; 95% confidential interval [CI], 1.66–3.36). Nevertheless, the comparisons of DMFS (pooled OR = 1.00; 95% CI, 0.76–1.31), and OS (pooled OR = 0.95; 95% CI, 0.79–1.14) between the IORT cohort with the WBI cohort were both not statistically significant. Conclusions Despite the drastically high 5-year oncological efficacy in both cohorts, the LRFS in the IORT cohort is significantly poorer than that in the WBI cohort, and DMFS and OS do not differ between cohorts.